Seek-Efficient I/O Optimization in Single Failure Recovery for XOR-Coded Storage Systems - Shen, Zhirong; Shu, Jiwu; Lee, Patrick P. C.; Fu, Yingxun (IEEE transactions on parallel and distributed systems, 2017)
Erasure coding provides an effective means for storage systems to protect against disk failures with low redundancy. One important objective for erasure-coded storage systems is to speed up single disk failure recovery. Previous approaches reduce the amount of read data for recovery by reading only a small subset of data. However, they often incur high disk seeks, which may negate the resulting recovery performance. We propose SIOR , a seek-efficient I/O recovery algorithm for improving the performance of single disk failure recovery. SIOR carefully balances the trade-off between the amount of read data and the number of disk seeks by considering the data layout at the multi-stripe level. It then greedily determines the data to read for recovery using Tabu search. Experiments show that SIOR achieves similar performance to the brute-force enumeration method while keeping high search efficiency. Also, SIOR reduces 31.8\sim 65.1 <inline-graphic xlink:href="shen-ieq1-2591040.gif"/> percent of disk seeks during recovery and provides up to 150.0 percent recovery speed improvement, when compared to a state-of-the-art greedy recovery approach.